Syberyjskie zesłanie jako przestrzeń i miejsce „przeznaczone na zatracenie” - Jędrychowska, Barbara (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2021)
In the Polish history of 19th and 20th century, the concept of Siberia was broad and connected with space but not always that of the geographical sort. A particular part of this space for many was the place of their Siberian exile. The 20thcentury brought this space and the places that were defined by it into an inhuman state. However, even in such circumstances, one could find examples proving that not all of those years were lost. This paper presents two Polish exiles, who were born and lived in two different periods and who were also connected by the space of Siberia, similar values and goals. Their experiences from the place of their Siberian exile serve as a testament that even such a difficult time could be used for “honest living and for the benefit of others.”
Keywords: Siberia in the 19th and 20th centuries; space of Siberia; a place of exile; Polish exiles; values and dreams